Identification of Small-Molecule Inhibitors of Neutral Ceramidase (nCDase) via Target-Based High-Throughput Screening. (January 2021) - Otsuka, Yuka; Airola, Michael V.; Choi, Yong-Mi; Coant, Nicolas; Snider, Justin; Cariello, Chris; Saied, Essa M.; Arenz, Christoph; Bannister, Thomas; Rahaim, Ron; Hannun, Yusuf A.; Shumate, Justin; et al.
There is interest in developing inhibitors of human neutral ceramidase (nCDase) because this enzyme plays a critical role in colon cancer. There are currently no potent or clinically effective inhibitors for nCDase reported to date, so we adapted a fluorescence-based enzyme activity method to a high-throughput screening format. We opted to use an assay whereby nCDase hydrolyzes the substrate RBM 14-16, and the addition of NaIO4 acts as an oxidant that releases umbelliferone, resulting in a fluorescent signal. As designed, test compounds that act as ceramidase inhibitors will prevent the hydrolysis of RBM 14-16, thereby decreasing fluorescence. This assay uses a 1536-well plate format with excitation in the blue spectrum of light energy, which could be a liability, so we incorporated a counterscreen that allows for rapid selection against fluorescence artifacts to minimize false-positive hits. The high-throughput screen of >650, 000 small molecules found several lead series of hits. Multiple rounds of chemical optimization ensued with improved potency in terms of IC50 and selectivity over counterscreen assays. This study describes the first large-scale high-throughput optical screening assay for nCDase inhibitors that has resulted in leads that are now being pursued in crystal docking studies and in vitro drug metabolism and pharmacokinetics (DMPK).